Corporate governance, state ownership and cross-listing: Evidence from Chinese A-share listed firms - Hongmei Xu (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2015)
This paper analyses the relationship between corporate governance, state ownership and cross-listing by using data from 2,113 Chinese A-share listed firms during the period 2008 to 2013. Firstly, corporate governance features in state-owned vs. non-state-owned and cross-listed vs. domestically-listed firms are examinde. Secondly, this paper investigates whether state ownership and cross-listing affect the sensitivity of the relation between corporate governance and firm value in Chinese listed firms. The effects are rather mixed. – – Der vorliegende Beitrag analysiert die Beziehung zwischen Corporate Governance, Staatseigentum und Zweitlisting anhand 2.113 chinesischer Firmen der Aktienklasse A in dem Zeitraum von 2008 bis 2013. Erstens werden Eigenschaften der Corporate Governance in staatlichen gegenüber nicht-staatlichen und doppelt gelisteten gegenüber nur inländisch gelisteten Unternehmen untersucht. Zweitens untersucht dieser Beitrag, ob Staatseigentum und Zweitlisting einen Einfluss auf die Beziehung von Corporate Governance und Unternehmenswert chinesischer Firmen haben. Die Effekte sind eher gemischt.
Keywords: G30; G34; M12; M50; P31; 650